2018
DOI: 10.3892/etm.2018.5926
|View full text |Cite
|
Sign up to set email alerts
|

Improved plaque neovascularization following 2-year atorvastatin therapy based on contrast-enhanced ultrasonography: A pilot study

Abstract: Abstract. The present study assessed changes in carotid plaque neovascularization following long-term atorvastatin therapy (20 mg/day) using contrast-enhanced ultrasonography (CEUS). In this prospective case series, seven males (mean age, 68±9 years) and three females (mean age, 67±10 years) with a total of 13 carotid plaques underwent standard ultrasonography and CEUS at baseline, as well as after 1 and 2 years of atorvastatin treatment. The same plaques were then examined using real-time CEUS. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(43 reference statements)
0
8
0
1
Order By: Relevance
“…During the 6 months of follow-up, we found no significant changes in IPN. A Japanese CEUS study found a non-significant trend toward reduced IPN in plaques that had been asymptomatic for >6 months ( 18 ), while another study demonstrated reduced IPN after 2 years of atorvastatin therapy ( 19 ). It is possible that 6 months of follow-up is insufficient to detect a decrease in IPN, as these changes are gradual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 6 months of follow-up, we found no significant changes in IPN. A Japanese CEUS study found a non-significant trend toward reduced IPN in plaques that had been asymptomatic for >6 months ( 18 ), while another study demonstrated reduced IPN after 2 years of atorvastatin therapy ( 19 ). It is possible that 6 months of follow-up is insufficient to detect a decrease in IPN, as these changes are gradual.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of microembolic signals (MES) on transcranial Doppler indicates ongoing embolization and is an independent predictor of future stroke in symptomatic and asymptomatic carotid artery disease ( 15 , 16 ). Data on the time course of MES and IPN in patients with carotid plaques are limited ( 17 19 ). We aimed to assess temporal changes in microembolization and neovascularization during a 6-month follow-up study and explored the utility of advanced neurosonology in acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…p l / k a r d i o l o g i a _ p o l s k a CEUS. All of them suggested reduced IPN after either 6-month statin therapy [40,64], or 24-month atorvastatin administration (20 mg/d) [65], or angiotensin-converting enzyme inhibitors and statins treatment [66]. Similarly, in 45 statin-naive patients with asymptomatic carotid atherosclerosis, 24-month rosuvastatin therapy (5-20 mg/d) reduced the MRI-based IPN [34].…”
Section: Neovascularizationmentioning
confidence: 99%
“…Так, Xu B, et al оценивали изменение неоваскуляризации АСБ СА на фоне длительной терапии аторвастатином (20 мг/сут.) и показали значительное уменьшение неоваскуляризации АСБ через два года наблюдения [38]. Авторы сделали вывод о том, что УЗИ с контрастным усилением может быть новым инструментом для оценки влияния терапии на состояние сосудов в клинических исследованиях.…”
Section: методические аспекты проведения исследованияunclassified